Measuring business development in developing countries: how and why the World Bank should revise its approach - Cárdenas, Mauricio (Henry Stewart Talks, 2023)
Doing Business report, World Bank, Foreign direct investing, Multinational corporations, Country rankings, Access to data, Food production, Bias towards manufacturing